Quasilinear parabolic equations with p(x)-Laplacian diffusion terms and nonlocal boundary conditions - RAHMOUNE, Abita; BENABDERRAHMANE, Benyattou (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
In this study, we prove the existence of local solution for a quasi linear generalized parabolic equation with nonlocal boundary conditions for an elliptic operator involving the variable-exponent nonlinearities, using Faedo-Galerkin arguments and compactness method. Mathematics Subject Classification (2010): 35K20, 35K59, 35B45, 35D30.